The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1128/aac.02606-18
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Evaluation of Solithromycin against Streptococcus pneumoniae Using Data from a Neutropenic Murine Lung Infection Model

Abstract: Solithromycin (CEM-101) is a novel fluoroketolide antimicrobial agent with activity against typical and atypical pathogens associated with communityacquired bacterial pneumonia. Using a neutropenic murine lung infection model, the objectives of this study were to identify the pharmacokinetic/pharmacodynamic (PK/ PD) index most closely associated with efficacy and the magnitude of such indices associated with solithromycin efficacy against Streptococcus pneumoniae. Plasma and epithelial lining fluid (ELF) sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(21 reference statements)
2
2
0
Order By: Relevance
“…Compared with the other macrolides and ketolides, the AUC values of nafithromycin in both plasma and ELF were substantially higher. Specifically, the mean nafithromycin AUC 24 is about three times greater than observed with solithromycin, which could be advantageous for nafithromycin in the treatment of bacterial pneumonia, although the MIC 90 is higher for solithromycin [65,67]. The pattern of intrapulmonary penetration of the AUC values of ELF and AM being circa 10-fold and 100fold higher, respectively, than total plasma concentrations for these two novel agents are consistent with previously reported findings for azithromycin, clarithromycin, and telithromycin.…”
Section: Nafithromycinsupporting
confidence: 89%
See 1 more Smart Citation
“…Compared with the other macrolides and ketolides, the AUC values of nafithromycin in both plasma and ELF were substantially higher. Specifically, the mean nafithromycin AUC 24 is about three times greater than observed with solithromycin, which could be advantageous for nafithromycin in the treatment of bacterial pneumonia, although the MIC 90 is higher for solithromycin [65,67]. The pattern of intrapulmonary penetration of the AUC values of ELF and AM being circa 10-fold and 100fold higher, respectively, than total plasma concentrations for these two novel agents are consistent with previously reported findings for azithromycin, clarithromycin, and telithromycin.…”
Section: Nafithromycinsupporting
confidence: 89%
“…The modeling supported a high AUC/MIC target attainment following administration of the oral dosing regimen of solithromycin 800 mg on day 1 and 400 mg once daily on days 2-5. Okusanya and colleagues performed a PK/PD analysis of solithromycin in a neutropenic murine lung infection model [65]. The observed solithromycin total drug ELF to unbound drug plasma AUC 24 ratio in mice was 2.7, which was considerably lower than solithromycin penetration in human lung ELF.…”
Section: Solithromycinmentioning
confidence: 99%
“…High target attainments for simulated ELF concentrations suggests that the oral dosing regimen evaluated in clinical trials (800 mg on day 1, followed by 400 mg on days 2–5) is appropriate for the treatment of CABP. Similar findings were observed for a previously developed population‐based PK model: net bacterial stasis and a 1‐log 10 colony forming unit reduction of ≥99.9% and 90.9%, respectively, for MIC values between 0.125 and 1 µg/mL . Although PBPK and population‐based PK modeling approaches are different, similar PK/PD relationships observed between the two models increases the confidence of our results.…”
Section: Discussionsupporting
confidence: 89%
“…These studies suggested that sutezolid had superior activity to linezolid [ 18 , 19 ]. A comparison of the activity of sutezolid and its metabolite U-101603 demonstrated that the latter had greater activity against nonreplicating persisters than its parent compound, which was more active in the log growth phase [ 20 ]. The addition of rifampicin was synergistic with sutezolid and was needed to prevent resistance associated with sutezolid monotherapy [ 21 ].…”
Section: Resultsmentioning
confidence: 99%